Protests Against Injustice In “The Outcast” Novel By Okky Madasari (2014): Liberal Feminism Approach - Ela Kristi Permatasari (Universitas Muhammadiyah Lampung, 2021)
This research is carried out to describe the role of liberal feminism in the Outcast novel. The outcast represents Okky Madasari (the writer) for those whose are banished because of their belief. This research is about a social problems which are faced by an Ahmadi as an excommunication. The social problems which are discussed in this research are injustice. The purpose of this research is to expose Maryam’s struggle to get justice for a religion organization called Ahmadi. .Based on the outcast novel the result of analysis shows that the role of liberal feminism is very important toward the social problem, social discrimination, criminality, educations, religion, economic and business, anxiety, psychoanalytic, traumatic experiences, sacrifice, and marriage norm.